A nano-structured RuO2/NiO cathode enables the operation of non-aqueous lithium–air batteries in ambient air. Issue 5 (21st March 2016) - Tan, P.; Wei, Z. H.; Shyy, W.; Zhao, T. S.; Zhu, X. B.
Abstract : A cathode composed of RuO2 nanoparticle-decorated NiO nanosheets not only catalyzes the oxygen reduction and evolution reactions, but also promotes the decomposition of the side products (LiOH and Li2 CO3 ), enabling a non-aqueous lithium–air battery to be truly operated in ambient air. Abstract : We report a cathode composed of RuO2 nanoparticle-decorated NiO nanosheets for a non-aqueous lithium–air battery. Unlike most of the previously reported non-aqueous lithium–air batteries that are operated with pure oxygen only, we demonstrate that the present cathode enables the battery to be truly operated in ambient air at 500 mA h g −1 for 200 cycles (800 h), with stable coulombic efficiency (100%) and high energy efficiency (∼75%). The stellar performance is attributed to the favorable combination of RuO2 nanoparticles and NiO nanosheets, which not only catalyzes the oxygen reduction and evolution reactions, but also promotes the decomposition of the side products, including lithium hydroxide and carbonate formed from water and carbon dioxide in the air during discharge.